The trauma caused by the Matebeleland massacre of 1982-1987 in Tsholotsho Zimbabwe and how the church can bring transformation using pastoral care - Masango, Maake J.S (University of Pretoria, 2013)
Dsecription (PhD)--University of Pretoria, 2010.